2D spatial optimisation of functionally graded materials used as insulators for field stress control. Issue 8 (1st October 2019) - Qasim, Syed Abdullah; Gupta, Nandini
Abstract : Functionally graded materials (FGMs) are expected to be useful in the electrical industry, especially for achieving an efficient electric field stress control. However, as these are relatively new materials, there are a number of unanswered research questions around them. A novel method to obtain an optimised spatial distribution of permittivity or electrical conductivity of FGMs used as insulators for electric stress control is presented in this study. The problem is envisaged as the realisation of two objectives viz., (i) to minimise maximum stress and (ii) to achieve a more uniform electric stress distribution. Permittivity or electrical conductivity of FGMs is considered as variables of optimisation and based on this a unique stochastically‐controlled multi‐objective particle swarm optimisation technique is developed. The spatial optimisation of the properties has been carried out in 2‐dimensions, which, unlike previous studies is more realistic. After validation with results available in the literature, it has been found that the electric field distribution in a cable termination is greatly improved by using stress control tube (SCT) having optimised permittivity gradation, which further improves by using SCT of optimised conductivity gradation.